2021
DOI: 10.3389/fmicb.2021.569020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hydrogen-Producing Bacteria in Tibetan Hot Springs, China

Abstract: Investigating the distribution of hydrogen-producing bacteria (HPB) is of great significance to understanding the source of biological hydrogen production in geothermal environments. Here, we explored the compositions of HPB populations in the sediments of hot springs from the Daggyai, Quzhuomu, Quseyongba, and Moluojiang geothermal zones on the Tibetan Plateau, with the use of Illumina MiSeq high-throughput sequencing of 16S rRNA genes and hydA genes. In the present study, the hydA genes were successfully amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The locations of study sites are shown in Fig. 3 (Luan et al, 2020), hot springs in the Southern Tibetan Plateau (Ma et al, 2021), water samples from the Three Gorges Reservoir (Gao et al, 2021), and wells in the Mahomet Aquifer, Illinois, USA (Yamamoto et al, 2019). Studies used field-collected samples except for those indicated by square symbols, which are for laboratory experiments or mesocosms.…”
Section: Analysis Of Local-scale Data For Different Environment Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The locations of study sites are shown in Fig. 3 (Luan et al, 2020), hot springs in the Southern Tibetan Plateau (Ma et al, 2021), water samples from the Three Gorges Reservoir (Gao et al, 2021), and wells in the Mahomet Aquifer, Illinois, USA (Yamamoto et al, 2019). Studies used field-collected samples except for those indicated by square symbols, which are for laboratory experiments or mesocosms.…”
Section: Analysis Of Local-scale Data For Different Environment Typesmentioning
confidence: 99%
“…Dashed lines represent fits with a slope of less than 0.01 V -1 . Numbers for datasets are (1) Bison Pool, Yellowstone National Park (unlike the other datasets, DNA was extracted from biofilm samples) (Swingley et al, 2012), (2) acidic and (3) circumneutral to alkaline New Zealand hot springs (Power et al, 2018), (4) Dallol Geothermal Area (hypersaline and moderate to extremely acidic water) (Belilla et al, 2019), (5) Copahue Volcano-Río Agrio (Lopez Bedogni et al, 2020;Massello et al, 2020), (6) Southwestern Yunnan (seven samples with pH > 7 and two moderately acidic samples) (Guo et al, 2021), (7) Eastern Tibetan Plateau (Guo et al, 2020), (8) Uzon Caldera (nine samples for acidic water and sediment and one high-pH sample) (Peltek et al, 2020), (9) Southern Tibetan Plateau (Ma et al, 2021), (10) Japan Hydrothermal Sediment (Omae et al, 2019). See Figure S1 for individual sample values.…”
Section: Global-scale Analysismentioning
confidence: 99%
“…If the location of source material for laboratory or mesocosm studies was not specified, the institutional address was used. Small open circles indicate sampling transects for paddy soils in East Asia ( 76 ), hot springs in the Southern Tibetan Plateau ( 38 ), and water samples from the Three Gorges Reservoir ( 25 ); small filled triangles represent 20 worldwide ports ( 14 ). ( b ) Eh–pH diagram for all environment types.…”
Section: Resultsmentioning
confidence: 99%
“…Colors are used to represent sample characteristics (acidic water, circumneutral to alkaline water, and sediment). Numbers for data sets are (1) acidic and (2) circumneutral to alkaline New Zealand hot springs ( 15 ), (3) Eastern Tibetan Plateau ( 36 ), (4) Uzon Caldera (including nine samples for acidic water and sediment and one high-pH sample) ( 37 ), and (5) Southern Tibetan Plateau ( 38 ).…”
Section: Resultsmentioning
confidence: 99%